The evaluation of hunters and foresters' knowledge of the possible ways of preventing Borrelia burgdorferi infections - Małgorzata Tokarska-Rodak; Mariia Shkilna; Monika Krajewska; Anna Pańczuk; Marcin Weiner; Ewa Pawłowicz; Mykhailo Korda; Ivan Klisch; Mykhailo Andreychyn (Nofer Institute of Occupational Medicine, 2020)
Background This study is aimed at evaluating the awareness among hunters and foresters concerning the activities undertaken for the prevention of Borrelia burgdorferi infections. Material and Methods The study group included 236 hunters from Poland and 339 foresters from Ukraine. The study was based on an original questionnaire including questions which concerned the applied methods of removing ticks attached to the skin, the kind of preventive measures undertaken to avoid tick bites, the evaluation of knowledge concerning the prevention of tick-borne diseases, as well as the participants' willingness to be educated on this issue. Results Removing a tick with a pair of tweezers by a simple vertical move was more frequently practiced by the hunters (16.5%). Spreading an oily substance over a tick to make it go out on its own was more often applied by the foresters (18.8%). The occurrence of erythema migrans was more frequently reported by the foresters (47.2%). Among the persons declaring no knowledge of the prevention of tick-borne diseases, 77.8% of the hunters and 61.5% of the foresters were willing to gain such knowledge, and 11.1% of the hunters and 21.2% of the foresters did not want any education on this issue. The hunters more often than the foresters applied repellents and checked their body after returning from green areas. Conclusions Education is needed in certain groups undertaking hobby or vocational activities in forest areas of Poland and Ukraine. It seems reasonable to undertake research on the preferences concerning the choice of repellents among the groups at risk of tick bites. Med Pr. 2020;71(1):59-68